Evolutionary perspective of Big tau structure: 4a exon variants of MAPT - Fischer, Itzhak (Frontiers in Molecular Neuroscience, 2022)
The MAPT gene encoding the microtubule-associated protein tau can generate multiple isoforms by alternative splicing giving rise to proteins which are differentially expressed in specific areas of the nervous system and at different developmental stages. Tau plays important roles in modulating microtubule dynamics, axonal transport, synaptic plasticity, and DNA repair, and has also been associated with neurodegenerative diseases (tauopathies) including Alzheimer’s disease and frontotemporal dementia. A unique high-molecular-weight isoform of tau, originally found to be expressed in the peripheral nervous system and projecting neurons, has been termed Big tau and has been shown to uniquely contain the large exon 4a that significantly increases the size and 3D structure of tau. With little progress since the original discovery of Big tau, more than 25 years ago, we have now completed a comprehensive comparative study to analyze the structure of the MAPT gene against available databases with respect to the composition of the tau exons as they evolved from early vertebrates to primates and human. We focused the analysis on the evolution of the 4a exon variants and their homology relative to humans. We discovered that the 4a exon defining Big tau appears to be present early in vertebrate evolution as a large insert that dramatically changed the size of the tau protein with low sequence conservation despite a stable size range of about 250aa, and in some species a larger 4a-L exon of 355aa. We suggest that 4a exon variants evolved independently in different species by an exonization process using new alternative splicing to address the growing complexities of the evolving nervous systems. Thus, the appearance of a significantly larger isoform of tau independently repeated itself multiple times during evolution, accentuating the need across vertebrate species for an elongated domain that likely endows Big tau with novel physiological functions as well as properties related to neurodegeneration.